The Analysis of the Effect of RIB Width and Channel Depth Design Modifications on CFD-Based Parallel Type Bipolar Plates for the Application of Proton Exchange Membrane Fuel Cell Stack Singles - Mochammad Tendi Noer Ramadhan; Amar Banu Mukhlisin; Belyamin; Radhi Maldzi; Abdul Azis Abdillah (MBI, 2025)
The use of large amounts of fossil fuels can pollute the air with significant amounts of carbon monoxide. Proton Exchange Membrane Fuel Cell (PEMFC) is an attractive alternative because it is able to generate high current with low working temperature, fast start-up time, no pollution, and good durability. In PEMFC systems, bipolar plates are one of the main and important components. This component facilitates the reactants to flow through the designed channel. This study aims to modify the parallel-type flow field design on the bipolar plate using CFD simulation in ANSYS, in order to improve the performance of PEMFC. While flowing through the bipolar plate, the reactants diffuse through the gas diffusion layer, thus connecting with the catalyst layer to generate protons and electrons in the anode and water and heat in the cathode through chemical reactions. The results of the study show that the variation of rib width and channel depth has a significant effect on the pressure distribution and hydrogen flow distribution.These findings can contribute to the improvement of flow distribution efficiency and pressure reduction